2019
DOI: 10.3390/chemengineering3020055
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Thermal Behavior of Layered Double Hydroxides Intercalated with Carboxymethylcellulose Aiming Bio-Carbon Based Nanocomposites

Abstract: Carboxymethylcellulose (CMC), a polymer derived from biomass, was intercalated into layered double hydroxides (LDH) composed by M2+/Al3+ (M2Al-CMC, M = Mg or Zn) and evaluated as precursors for the preparation of biocarbon-based nanocomposites by pyrolysis. M2Al-CMC hybrids were obtained by coprecipitation and characterized by X ray diffraction (XRD), vibrational spectroscopies, chemical analysis, and thermal analysis coupled to mass spectrometry. Following, pyrolyzed materials obtained between 500–1000 °C wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
2
12
0
1
Order By: Relevance
“…Similar to MgAl-LDH, thermal treatment on ZnAl-LDH caused the partial collapse in lamellar structure through degassing. Calcination at moderate temperature from 300 °C to 600 °C resulted in divalent metal oxide (ZnO) [ 62 , 63 , 64 ]. Different from MgAl-MMO, however, the ZnAl-MMO tends to have lower specific surface area ( Figure 1 (Ab)).…”
Section: Specific Surface Area Of Mmo Prepared From Calcined Ldhmentioning
confidence: 99%
“…Similar to MgAl-LDH, thermal treatment on ZnAl-LDH caused the partial collapse in lamellar structure through degassing. Calcination at moderate temperature from 300 °C to 600 °C resulted in divalent metal oxide (ZnO) [ 62 , 63 , 64 ]. Different from MgAl-MMO, however, the ZnAl-MMO tends to have lower specific surface area ( Figure 1 (Ab)).…”
Section: Specific Surface Area Of Mmo Prepared From Calcined Ldhmentioning
confidence: 99%
“…The TGA curve shows the total wei loss that occurred throughout the two stages. In the first stage, the water was lost through three steps [38]. It was found that wt.%, 7 wt.% and 8.3 wt.% were lost at 107 °C, 150 °C and 191 °C, respectively.…”
Section: Thermal Analysesmentioning
confidence: 99%
“…Additionally, DTA revealed two endotherm peaks at 250.6 °C and 307.9 °C, confirming the presence of two interlayered anions, c nate and nitrate, agreeing with the FTIR data. In the first stage, the water was lost through three steps [38]. It was found that 4.6 wt.%, 7 wt.% and 8.…”
Section: Thermal Analysesmentioning
confidence: 99%
“…Since Mg-Al-based LDHs also find use in drug delivery and biomedical imaging [9,11], the knowledge of the antibacterial activity seems to assume, like for bioactive glasses [12,13], a crucial importance and needs to be further investigated. On the other hand, some of these LDHs may intercalate suitable molecules and a thermal treatment of the so-obtained precursor materials may convert them into very promising oxides or composites [14,15]. The thermal activation of a LDH by calcination in a wide temperature range that usually is between 300 and 500 °C causes the release of water due to condensation of hydroxyl groups resulting in the formation a mixed metal oxides [16,17].…”
Section: Introductionmentioning
confidence: 99%